Pengaruh Fraud Hexagon Model Terhadap Indikasi Financial Statement Fraud - Indriyani Puspaningrum; Marsellisa Nindito; Muhammad Yusuf (Jurnal Riset Akuntansi, 2024)
The purpose of this study was to test and determine the effect of stimulus, opportunity, rationalization, capability, ego, and collusion on indications of financial statement fraud. This study uses purposive sampling in determining the sample with secondary data sources in the form of financial reports and annual reports of infrastructure companies listed on the Indonesia Stock Exchange (IDX) and the pages of each company during 2020 - 2022 with the final number of observations totaling 143 data. This study uses panel data regression analysis techniques in the Eviews 13 data processing application. The results of hypothesis testing in this study indicate that stimulus and opportunity have a positive effect on indications of financial statement fraud. While rationalization, capability, ego, and collusion do not affect indications of financial statement fraud. This research has practical implications for companies, investors, governments, and auditors in examining solutions to crucial problems in the stimulus and opportunity variables that indicate financial statement fraud because it is an evaluation of the level of ROA and NOIR proxies..